Utilização de limites de retenção superior a 5% do patrimônio líquido ajustado das companhias de seguros - Falcão, Marcos (2023)
The objective of this dissertation is to demonstrate the possibility of adopting a Retention Limit higher than 5% of the Insurer's Adjusted Shareholders' Equity, if there is no significant impact on the probability of bankruptcy. The analyzes were carried out considering Insurance companies with three distinct compositions in the origin of the Capital, namely: Independent Insurance company, that is, with national capital and not linked to the Bank, Insurance company with capital linked to the Bank and Insurance company with Capital of foreign origin, in this case, of capital and shareholding of foreign origin. The studies carried out simulate the result of the Insurer based on scenarios of increased loss ratio resulting from the consequent increase in levels for the Retention Limits, using the Cramér-Lundberg model. In the results calculated for the simulations, it was verified that the increase in the retention limit to 7.5% or 10.0% in relation to the Adjusted Shareholders' Equity did not have a significant impact on the probability of bankruptcy of these Insurers. Bearing in mind the concern about solvency when using Retention Limits greater than 5% of the PLA, the research was able to establish a simple model for predicting a possible impact on the solvency of Insurers